A new species of Boiga (Serpentes: Colubridae) from the Southern Western Ghats of India with a molecular phylogeny and expanded characterisation of related species - Ganesh, S.r.; Mallik, Ashok Kumar; Achyuthan, N.s.; Shanker, Kartik; Vogel, Gernot (Zootaxa, 2021)
We conducted a molecular phylogenetic study on the Boiga ceylonensis group from the Western Ghats of India, building on a recent morphology-based study. Our analysis supports previous work in elucidating the phylogenetic position of B. nuchalis and B. beddomei s. str. (of Matheran, Western Ghats) as clustering closely with B. ceylonensis, while B. flaviviridis clustered with the Sri Lankan taxon close to B. ranawanei. Additionally, our phylogenetic study revealed the presence of an undescribed taxon in the Southern Western Ghats, more closely related to B. ceylonensis than to any other sampled taxon, including sympatric congeners. This new taxon is described here as a new species Boiga whitakeri sp. nov. from the Devar Malai–Anaimalai hill complex. Based on molecular and morphometric studies, we expand the description of the recently described B. thackerayi as inhabiting almost the entire stretch of the Western Ghats. We also complement the diagnoses of B. nuchalis and B. flaviviridis, and determine the phylogenetic position of B. thackerayi with molecular data.